Legal Aspects of Environment in Indonesia: an Efforts to Prevent Environmental Damage and Pollution - Arifin Maruf (Lembaga Contrarius Indonesia, 2021)
Pollution and destruction of the environment are some of the severe threats to the conservation of the environment in Indonesia. The disturbed environmental balance needs to be restored as the giver of life and welfare benefits society by improving environmental protection, community development, and optimization of environmental law enforcement. It aims to maintain the existence of nature and aimed at solving environmental problems in Indonesia, primarily the caused by human activity. this case could be through civil, administrative, or criminal law so that it can cope with and take action against perpetrators of pollution, and the destruction of the environment and create a good environment, healthy, beautiful and comfortable for all people. Keywords: Environmental Law; Environmental Damage; Indonesia.